Little Nicky [videorecording (DVD)] - Simonds, Robert, 1964-; Giarraputo, Jack; Herlihy, Tim; Sandler, Adam; Brill, Steven; Arquette, Patricia, 1968-; Keitel, Harvey; Ifans, Rhys, 1967-; Lister, Tiny; Dangerfield, Rodney, 1921-2004; Van de Sande, Theo; Gourson, Jeff; et al. (New Line platinum series., 2001)
When your mother is an angel and your father is the devil, life can be really confusing. For Little Nicky, it just got a whole lot worse. His two evil brothers have just escaped from Hell and are wreaking havoc on an unsuspecting earth. His dad is disintegrating and it's up to Nicky to save him and all of humanity. Can Nicky find his inner evil in time to save the world?